ANALISIS EKONOMI KELEMBAGAAN DALAM SISTEM PASCA-PRODUKSI DAN PEMASARAN HASIL TERNAK: STUDI KASUS DI RPH AKBAR JAYA KOTA MAKASSAR - Nurhapsa, Nurhapsa; Hastang, Hastang; Sirajuddin, Sitti Nurani; Rasyid, Ilham; Syarif, Ilham; Utama, A. Della Riski; Izzah, A. Nurul; Mukhlis, Mukhlis (Program Studi Agribisnis Fakultas Pertanian, 2025)
The beef cattle industry plays a very important role in meeting the need for beef as one of the main sources of protein for the community. Post-production institutions for beef cattle include the entire system of organizations, institutions, and mechanisms involved in the processing, packaging, distribution, and marketing of beef products after the cattle are slaughtered. The importance of post- production institutions for beef cattle is also increasingly relevant with the increasing demand for beef, both in the domestic and international markets. The livestock products from RPH Dg Lalla include beef which is still the main product with the highest economic value. However, other parts such as bones, skin, offal, feet, and heads of cattle also contribute significantly to supporting the economy of livestock farmers and business actors. The use of all parts of the cattle, if managed properly, can provide great added value while reducing livestock waste. The flow of products starts from the collector as the provider of cattle, then sells the cattle at the RPH. The average cattle slaughter at RPH UD. Akbar Jaya is 20 per day depending on market demand. Then the RPH carries out its functions such as supervision and inspection of beef that is slaughtered every 02.00-05.00 in the morning. Furthermore, the beef is distributed by the butcher to consumers through retailers in traditional markets in Makassar City and processing traders to be processed such as meatballs, coto and others. The buyers of the processed beef products are the end consumers.